2018
DOI: 10.1128/aac.00491-18
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro MIC Values of Rifampin and Ethambutol and Treatment Outcome in Mycobacterium avium Complex Lung Disease

Abstract: Although it is known that the MICs of rifampin and ethambutol are poorly correlated with the clinical response in complex (MAC) lung disease (MAC-LD), evidence for this is limited. This study investigated the association between treatment outcome and the MICs of rifampin and ethambutol in patients with MAC-LD. Among patients diagnosed with macrolide-susceptible MAC-LD between January 2008 and December 2013, 274 patients who were treated with a standard regimen for ≥12 months until August 2017 and whose MIC res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 39 publications
4
14
0
1
Order By: Relevance
“…In our study, clarithromycin showed good inhibitory activity against all MAC isolates, consistent with previous studies [19,20]. The resistance rate of MAC isolates against rifampin was 82.9% (92/111), which was in agreement (78.9%; 216/274) with a previous study [21]. Unlike rifampin, rifabutin showed a better antimicrobial activity and was recommended as an alternative to rifampicin, especially for disseminated MAC infections, for patients infected with MAC [22].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, clarithromycin showed good inhibitory activity against all MAC isolates, consistent with previous studies [19,20]. The resistance rate of MAC isolates against rifampin was 82.9% (92/111), which was in agreement (78.9%; 216/274) with a previous study [21]. Unlike rifampin, rifabutin showed a better antimicrobial activity and was recommended as an alternative to rifampicin, especially for disseminated MAC infections, for patients infected with MAC [22].…”
Section: Discussionsupporting
confidence: 91%
“…In the management of MAC-LD, the clinical utility of drug susceptibility tests has not been established except for CLR [27]. Recently, an MIC ≥8 μg/mL for both EMB and RIF reflected an unfavorable response to standard treatment for MAC-LD [28]; however, it was not associated with negative sputum conversion in our patients with refractory MAC-LD. With regard to fluoroquinolone, MXF susceptibility break points, defined only by the Clinical and Laboratory Standards Institute, were not predictors of treatment response for refractory MAC-LD [15].…”
Section: Discussionmentioning
confidence: 91%
“…It must be mentioned that for rifabutin and rifampin, the concentration range tested in broth does not cover the entire MIC distribution, either because concentrations are too high (rifabutin) or too low (rifampin) (Figure 1). However, despite overall high in vitro MICs, it has been shown that rifamycins and ethambutol do prevent selection of clarithromycin resistance (May et al, 1997;Gordin et al, 1999;Benson et al, 2003), and a recent study reported a better clinical response when rifampin and/or ethambutol MICs were below 8 mg/L (Kwon et al, 2018). If these results are confirmed, this concentration could be used as a clinical breakpoint.…”
Section: Discussionmentioning
confidence: 99%